Comparison of the treatment performance of bio-substrate based and meadow brown soil based subsurface infiltration systems for domestic wastewater treatment. - Li, Ying-Hua (Water Science and Technology)
To foster the practical development of subsurface wastewater infiltration (SWI) systems in China, two systems were implemented on the campus of Shenyang University. The bio-substrate filled SWI (BSWI) and meadow brown soil filled SWI (MSWI) system operated under the same operation mode. According to the 12-month experimental results, the bio-substrate had much higher potential to be a good substrate as compared to the meadow brown soil. The maximum adsorbing capability for NH4+-N of the bio-substrate was 0.724 mg/g, while for the meadow brown soil, the maximum value was 0.471 mg/g. The amounts of nitrifying and denitrifying bacteria of the BSWI were one order of magnitude higher than that for the MSWI. Ammonia, nitrite and nitrate nitrogen concentrations implied nitrification?denitrification process went well in the BSWI. Moreover, the BSWI system maintained efficient pollutants removal, the mean removal efficiencies were 92.3 ± 1.5%, 96.5 ± 3.1%, 90.0 ± 2.1%, 78.6 ± 1.2%, 91.2 ± 1.1% and 99.7 ± 1.0% for COD, BOD5, NH4+-N, TN, TP and SS, respectively. As compared with the MSWI system, pollutant removal efficiencies improved by 26.8 ± 2.3% for NH4+-N, 33.8 ± 1.7% for TN, 22.4 ± 1.4% for COD, 26.0 ± 3.5% for BOD5 and14.7 ± 2.9% for TP, respectively.